2020
DOI: 10.1017/s0950268820000539
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality in carriage of extended-spectrum β-lactamase-producing Escherichia coli and Klebsiella pneumoniae in the general population: a pooled analysis of nationwide cross-sectional studies

Abstract: Infections due to extended-spectrum β-lactamase-producing Enterobacteriaceae (ESBL-E) are often preceded by asymptomatic carriage. Higher incidences in enteric infectious diseases during summer have been reported. Here, we assessed whether the presence of seasonality in intestinal ESBL-Escherichia coli/Klebsiella pneumoniae (ESBL-E/K) carriage in the general Dutch population exists. From 2014 to 2017, the faecal carriage of ESBL-E/K in healthy individuals was determined in three cross-sectional studies in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 25 publications
0
15
1
Order By: Relevance
“…The estimated prevalence of 6.29% [95% IC: 4.34–9.02%] of ESBL- E. coli in companion animals can be considered lower compared to estimations in livestock (50%–70%) [ [152] , [153] , [154] , [155] ], and in humans (2%–46%) [ [156] , [157] , [158] , [159] ]. No statistical differences of prevalence were observed between dogs (6.87%) and cats (5.04%) and we did not observe variation on the prevalence rates of ESBL- E. coli either in dogs or cats over years (meta-regression, p > 0.1).…”
Section: Discussionmentioning
confidence: 99%
“…The estimated prevalence of 6.29% [95% IC: 4.34–9.02%] of ESBL- E. coli in companion animals can be considered lower compared to estimations in livestock (50%–70%) [ [152] , [153] , [154] , [155] ], and in humans (2%–46%) [ [156] , [157] , [158] , [159] ]. No statistical differences of prevalence were observed between dogs (6.87%) and cats (5.04%) and we did not observe variation on the prevalence rates of ESBL- E. coli either in dogs or cats over years (meta-regression, p > 0.1).…”
Section: Discussionmentioning
confidence: 99%
“…Seasonal variation in excretion of ESBL/AmpC is poorly described in veterinary medicine. A study in a human population reported that carriage of ESBL E. coli and Klebsiella pneumoniae was highest in the months at the end of summer/beginning of autumn (August/September) (54). Another study reported higher levels of excretion of ESBL between July and September, although this was inversely correlated with use of antimicrobials (55).…”
Section: Discussionmentioning
confidence: 99%
“…Seasonality of bacterial infections has been investigated almost exclusively in acute care settings, and mostly limited to patient isolates, where seasonal trends have been established for several pathogens in a range of geographical settings ( 1 , 2 , 8 , 9 ), including antimicrobial-resistant strains ( 10 ), often linking higher temperatures to increases in rates of infections, especially those due to gram-negative bacteria. Notably, a study focused on S. aureus infections reports seasonality in hospitals, but not in NHs ( 4 ), highlighting the importance of obtaining specific data in post-acute and long-term care.…”
Section: Discussionmentioning
confidence: 99%